Performance assessment of passive heating and cooling techniques for underground shelter in equatorial climate - Mukhtar, Azfarizal; Ng, Khai Ching; Yusoff, Mohd Zamri; Wah, Yen Tey; Lit, Ken Tan (Akademia Baru, 2019)
Underground shelter serves as a specialized building structure that can provide either heating or cooling to occupants during different climates depending on the requirements. In this study, the CFD model of the 3D underground shelter was simulated at different seasons of the year in Malaysia. Initially, the soil temperature distributions at various depths were numerically investigated using the Kasuda Model; this model showed that at a depth of more than 10 m, the soil temperature remains constant. The soil thermal properties were considered in our numerical model simulated using ANSYS Fluent. The CFD model was firstly validated with the published experimental data, before it was used to simulate the passive heating and cooling operations within the underground shelter. The results indicated that the temperature of the underground shelter ranged between 27.80℃ and 32.10℃ from day to night. This assessment was evaluated in the coldest and warmest months of the year. Finally, the simulated room temperatures were compared against the standard Malaysian comfort temperature. It was found that natural ventilation alone could not assure a good thermal comfort level within the underground shelter.